Delaying emergence of resistance to KRAS inhibitors with adaptive therapy: “treatment-to-contain” instead of “treatment-to-cure” - Hamdi, Amir Imran Faisal; Stanslas, Johnson (Tech Science Press, 2022)
KRAS mutations are among the most common oncogenic abnormalities in cancer. Until recently, drug discovery pursuing KRAS did not produce therapeutic benefits for patients. Specific KRAS inhibitors, such as sotorasib and adagrasib, which bind covalently to codon 12 of substituted glycine to cysteine residue of the protein (G12C), have been approved by the FDA recently for the treatment of lung cancers. Binding of these drugs to the protein inhibits the activation of the GDP-bound inactive state to the GTP-bound active state. Phase 1/2 trials have shown potential anti-tumor activity, particularly in patients with previously treated non-small cell lung cancer. Acquired resistance, on the other hand, is inevitable, and the mechanisms include new KRAS mutations such as Y96D/C and other RAS-MAPK effector protein abnormalities. “Adaptive Therapy,” an ecologically inspired concept, focuses on extending the treatment-free period in a treatment course to delay the emergence of resistance. This review focuses on acquired mechanisms of resistance to KRAS G12C inhibitors, as well as the application of adaptive therapy in the treatment of KRAS-mutated patients to maintain acquired resistance sub-clones and extend progression-free survival.